Perhitungan Cepat Kelimpahan Acanthaster planci di Pulau Sombori, Morowali, Sulawesi Tengah - Zamani, Nevyati P.; Subhan, Beginer; Rachma ati, Rita; Jansit, Afifah F. (Jurnal Sumberdaya Akuatik Indopasifik, 2024)
Acanthaster planci is one of the most potential causes of coral reef damage in Indonesia. The presence of A. planci in Indonesia has been reported with a large population and preys on corals with large numbers. This research as conducted in order to provide information quickly related to the category of A. planci hems in the Sombori tribe. The monitoring method used is the time s imming method hich is carried out for 2x10 minutes. Categorization of outbreak determination using threshold approach developed in the ORANET (Oceania Regional Acanthaster Network) program. Monitoring the abundance of A. planci as carried out in seven locations with 10 observation points, namely Dongkalan Kecil Island with 123 individuals, Dongkalan Besar Island with 5 individuals, Mbokita Island with 60 individuals, Kayangan Island with 7 individuals, Red Sand Beach with 5 individuals, Air Kiri Beach with 6 individuals, and Goa Alo Beach with 6 individuals. The high number of A. planci individuals is only found on 2 islands, namely Dongkalan Kecil Island and Mbokita Island. The number of A. planci on these t o islands is included in the category of possible outbreaks and is included in the category of threatening coral reef ecosystems. The condition of coral reefs on Dongkalan Island is small dominated by dead corals thought to be due to predation of A. planci. hile on Mbokita Island, the condition of coral reefs is not dominated by dead corals but there are many remnants of predation on corals.